The Influence of Islamic Religious Education on Students’ Mental Health Awareness - Sinta Nur Arifin; Muhammad Wildan Shohib (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research focuses on the influence of Islamic Religious Education on students’ mental health understanding at SMK Negeri 1 Sukoharjo, the significance of Islamic spirituality and the rise in mental health issues among teenagers serve as the study's backdrop. values to maintain psychological equilibrium. 159 students in grade XII participated in the study, which took a quantitative approach and collected data using a Likert scale questionnaire. The outcome of the reliability and validity tests demonstrated that each instrument was appropriate for use. Regression analysis criteria were satisfied by the preparatory tests, which comprised heteroscedasticity, linearity, and normality tests. The t-test results indicate that Islamic Religious Education has a significant effect on students’ mental health awareness, as shown by a significance value of 0.000, which is lower than 0.05. The correlation test's Pearson Correlation value of 0.390 indicated a favorable connection with a low level of connection strength the Islamic Religious Education variable only contributes 0.1% to mental health awareness, according to the measure of determination, suggesting that other factors outside the purview of this study have a bigger influence on students' mental health. This study confirms that the internalisation of Islamic values through Islamic Religious Education plays a role in building mental health awareness, even though its influence is not statistically significant.